Mikhail Saltykov-Shchedrin’s “The History of a Town” and “Mikhailu Yevgrafovichu” by Vyacheslav Pyetsukh: The Russian Mentality - Собенников, Анатолий (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article is devoted to Vyacheslav Pyetsukh’s reception of Mikhail Saltykov-Shchedrin’s satire The History of a Town. In The History of the Town of Glupov in New and Modern Times and The Town of Glupov in the Last Ten Years Pyetsukh develops the motif of irrationality in Russian government and public life. The author also analyzes the semantic and axiological aspects of ‘Russian-ness’ in Pyetsukh’s texts.